29. QUALITY OF LIFE BEFORE AND AFTER INTERVENTION IN URINARY STONE PATIENTS AT TUYEN QUANG PROVINCIAL GENERAL HOSPITAL IN 2025 (Vietnam Journal of Community Medicine, 2025)
Objective: Description of quality of life before and after intervention in patients with urinary stones at Tuyen Quang provincial General Hospital in 2025.Subjects and methods: Cross-sectional descriptive study with 110 patients with urinary stones treated at the hospital from January to June 2025.Results: Before the intervention, the average score of the overall quality of life of the patients was 37.64 ± 11.23 points out of a total of 100 points, of which the average score of the quality of life for mental health was 42.61 ± 10.85 points, higher than the average score of the quality of life for physical health was 32.67 ± 12.13 points. After 1 month of intervention, the average score of the overall quality of life of the patients increased to 48.40 ± 4.73, of which the average score of the quality of life for physical health and mental health increased to 49.96 ± 8.43 and 49.83 ± 5.17 points, respectively. The increase after the intervention compared to before the intervention was statistically significant (p < 0.05).Conclusion: The quality of life of patients was low at the time before the study but was significantly improved after the intervention. The study results show the importance and necessity of health education for patients with urinary stones.
Keywords: Quality of life, urinary stones, intervention.